Pengambilan Paksa Oleh Debt Collector Atas Benda Jaminan Debitur Yang Dibebani Fidusia Pasca Putusan Mahkamah Konstitusi NO.18/PUU-XVII/2019 - Ni Kadek Riawati; I Nyoman Putu Budiartha; I. B Gede Agustya Mahaputra (Fakultas Hukum Universitas Warmadewa, 2025)
Forced retrieval by debt collectors of debtors' collateral objects bound by fiduciary agreements, especially after the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019. The main focus of this research is to analyze the legal implications and changes in the forced retrieval process after the decision. The problem formulation in this research is the current legal arrangements and the execution of fiduciaries who have defaulted after the issuance of the decision. The research method used by normative law involves literature study, analysis of the content of Constitutional Court decisions, and tracing related legal developments. The results of the study show that the Constitutional Court's decision has a significant impact on the procedures and responsibilities in forced collection by debt collectors. Changes in the legal basis and protection of debtors' rights are in the main spotlight, while the principles of justice and proportionality are also considered. This research contributes to a further understanding of the legal consequences of the Constitutional Court's decision on the practice of forced expropriation by debt collectors. debt collectordebt collector.